"NO US WITHOUT YOU!": on recontextualizing border visuality. Issue 1 (2nd January 2021) - Alvarado, Raisa Fernanda
ABSTRACT: This essay explores border visuality as utilized by the Los Angeles based nonprofit "NO US WITH YOU!" for the sake of broadening pejorative conceptualizations of the Latina/o/x immigrant body. Through an exploration of the organization's social media efforts and through an analysis of the organization's visuals of border children, the visuality of food justice, and the visual of "coalition-inmotion" this article argues for the potentiality of visual rhetoric in the twenty-first century.